Gambaran Fatherless dalam Pembentukan Self-Compassion pada Siswa SMP - Masita, Nurul; Pribadi, Imam; Kadir, Abdul (LITPAM, 2026)
Masa remaja merupakan waktu krusial di mana individu membutuhkan dukungan keluarga yang stabil, namun fenomena fatherless atau ketidakhadiran figur ayah, baik secara fisik maupun emosional, memberikan dampak psikologis serius terhadap perkembangan remaja. Penelitian ini bertujuan untuk mendeskripsikan gambaran self-compassion serta menganalisis faktor-faktor yang dihadapi dalam pembentukannya pada siswa SMP yang mengalami kondisi fatherless. Menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologi deskriptif, penelitian ini melibatkan informan di SMPN 5 Sepakat yang dipilih melalui teknik purposive sampling. Teknik pengumpulan data dilakukan melalui observasi partisipatif moderat, wawancara tidak terstruktur, dan dokumentasi, dengan teknik analisis menggunakan triangulasi data untuk menjaga kredibilitas hasil. Hasil penelitian menunjukkan bahwa gambaran self-compassion pada informan secara umum berada pada kategori rendah, yang ditandai oleh dominasi self-judgment yang kuat, rendahnya perasaan common humanity, serta kecenderungan larut dalam emosi negatif (over-identification). Faktor penghambat utama meliputi pola pengasuhan negatif dari orang tua yang tersisa, perundungan dari teman sebaya, dan ketidakstabilan ekonomi pasca-kehilangan figur ayah. Meskipun demikian, terdapat faktor pendukung berupa kehadiran figur pengganti yang suportif dan kemampuan menggunakan afirmasi positif sebagai bentuk resiliensi. Penelitian ini mengimplikasikan pentingnya layanan konseling sekolah yang proaktif dalam mendampingi siswa dengan kerentanan psikologis akibat kondisi keluarga yang tidak utuh guna meningkatkan kesejahteraan psikologis mereka. Early adolescence is a developmental period that requires stable family support, including the presence of a father figure as a source of emotional security, validation, and relational learning. Fatherlessness may be experienced as physical absence or emotional disconnection and may shape how adolescents treat themselves when facing failure, social pressure, and rejection. This study aimed to describe the lived experience of fatherlessness and the tendency of self-compassion among female junior high school students, as well as to identify the accompanying risk and protective factors. A qualitative approach with a descriptive phenomenological design was employed. Three female students at SMPN 5 Sepakat who experienced fatherlessness due to parental divorce were selected purposively. Data were collected through in-depth semi-structured interviews, moderate participant observation, and documentation. The data were analyzed through phenomenological procedures including transcription, repeated reading, horizontalization, identification of meaning units, thematic clustering, textural-structural description, and formulation of the essence of experience. Trustworthiness was maintained through methodological triangulation, contextual source triangulation, limited member checking, an audit trail, and researcher reflexivity. The findings indicate that participants’ experiences of fatherlessness were associated with a less optimal development of self-compassion, particularly through dominant self-judgment, feelings of being different from peers, and a tendency to be overwhelmed by negative emotions. The risk factors included critical parenting, social comparison, peer bullying, and family economic pressure. Nevertheless, surrogate figures, close peer support, expressive activities, positive affirmation, and future aspirations emerged as protective resources. This study highlights the need for school counseling services that are sensitive to fatherlessness and oriented toward strengthening self-kindness, common humanity, and mindfulness.